Evaluation of theophylline clearance in asthmatic or COPD patients admitted to emergency ward of Kerman Afzalipour hospital in 2006 - seyed mojtaba Sohrevari (Yafteh, 2009)
Background: Theophylline is one of the oldest drugs that is used to treat asthma and COPD. Theophylline metabolism can alter by some of the drugs and diseases. Severe theophylline side effects are usually related to plasma concentration higher than 20 mg/L. The present study was done to determine aminophylline clearance and the drug use evaluation in Afzalipour hospital. Materials and Methods: In this cross-sectional study 21 asthmatic or COPD patients were enrolled. 2 blood samples were drawn at 15 minutes and 24 hrs after completing aminophylline loading dose and starting maintenance dose infusion. Serum theophylline concentration were determined using HPLC and drug clearance was calculated by Chiou methods and compared with theophylline clearance based on population pharmacokinetic study. Results: Mean patients age were 57±18 years. Mean theophylline concentration in the two samples were 9.1±4 and 5.1 ±3.3 mg/L respectively. Our patients clearance was 4.2±2.2 L/hr and there was no statistically significant difference with theophylline clearance (3.1±1) based on population pharmacokinetic study (P=0.075). Conclusion: Based on our study there was not rational and logical usage of aminophylline in the our patiens. In 62% of the patients’ serum, theophylline level were less than 5 mg/L. It is suggested that Therapeutic Drug Monitoring must be used in patients who receive intravenous aminophylline specifically in the critically ill patients, to prevent drug toxicity and to ensure about drug efficacy.